Clinical Profile And Aetiology of Acute Kidney Injury Developing In Patients Hospitalized Due To Non-Renal Cause With Pre-Existing Normal Renal Function - Akter, Sanzida; Kamal, Mohammad Mostafa (Journal of Dhaka Medical College, 2024)
Background: Acute kidney injury (AKI) is a common complication in patients hospitalized for non-kidney disease and having normal renal function. Early detection of development of deteriorating renal function and assessment of its cause can help to manage the cases effectively and can prevent further kidney damage or progression to end stage renal failure. Methods: This observational study was done on 50 patients selected from the departments of Medicine and Nephrology of Dhaka Medical College (DMCH) and BSMMU, from June 2012 to November 2012. Patients were included in the study who developed clinical features and biochemical findings of acute kidney injury, while being admitted with various non-renal diseases and had previous normal renal function. Results: In this study the cause of deterioration of renal function was Sepsis in 44.0% of the patients, 42.0% had fluid loss, 6.0% had used nephrotoxic drugs, 4.0% had hepatitis, 2.0% patients each had pancreatitis and insect bite respectively. 40% of the patients were above 40 years of age, 54% were male. Vomiting was present in 42% of the patients and diarrhoea in 20% of the patients. 26% patients had DM and 22% had hypertension. Conclusion: Sepsis and hypovolemia were the common causes of developing acute kidney injury in the hospital. In-hospital mortality was 18.0% and 22.0% patients developed CKD after three months follow-up. J Dhaka Med Coll. 2023; 32(1) : 85-91